Strategies to Improve Service Quality in Improving Accessibility at the Pulo Brayan Health Center - Wirdah Muhammad Syukri Alghiffary; Dewi Agustina; Delfriana Ayu Astuty (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Accessibility of health services is an important aspect in providing quality primary health services at the Health Center. However, limited infrastructure, human resources, and service management continue to pose challenges to improving service quality. This study aims to analyze strategies to improve service quality to improve the accessibility of health services at the Pulo Brayan Health Center. This study uses a qualitative approach with a descriptive method. Informants were selected using purposive sampling techniques, consisting of the Head of the Health Center, general practitioners, and patients as service users. Data collection was carried out through in-depth interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that the strategy to improve service quality is implemented through the implementation of standard operating procedures (SOPs), the use of the JKN Mobile application to facilitate registration, the division of tasks of health workers according to competencies, the provision of priority services for vulnerable groups, and the strengthening of therapeutic communication and patient education. Even so, there are still a number of challenges, such as limited facilities and health workers, low public awareness of routine health check-ups, communication barriers, and relatively long waiting times for services. This study concludes that the implementation of integrated service strategies supported by the use of digital technology and patient-centered services, contributes to increased accessibility of healthcare services. However, further strengthening of facilities, human resources, and public education is still needed to optimize the quality of services at the Health Center.